Multiple brainstem infarctions in a boy caused by angiitis of the basilar artery. Issue 2 (7th June 2010) - Tsuji, Masahiro; Tamura, Takuya; Yoshida, Takeshi; Haruta, Tsunekazu
Abstract : A 13-year-old boy was admitted to our hospital with altered states of consciousness coupled with a headache and nausea. Upon admission, the patient was afebrile and comatose with a decorticated posture and was subsequently intubated. All routine laboratory tests and cerebrospinal fluid analyses were normal. Brain T2-weighted MRI (figure 1A ) revealed multiple hyperintense signals in the brainstem and cerebellum. A single gadolinium-enhanced lesion was observed in the left occipital lobe. These observations were indicative of acute disseminated encephalomyelitis (ADEM) and we subsequently started methylprednisolone pulse therapy. In the follow-up MRI study, the lesions were necrotic, suggesting changes after a stroke rather than ADEM. The MR angiography (figure 1B ) and the conventional cerebral angiography (figure 1C, D ) performed on days 25 and 28, respectively, revealed segmental stenoses ("beading") of the basilar artery and the left middle cerebral artery and the near occlusions of both posterior cerebral arteries with thrombus adjacent to the basilar artery bifurcation. No angiographic abnormalities were observed in the extracranial carotid and renal arteries. We diagnosed the lesions as angiitic infarctions and started plasma exchange and antiplatelet therapy. Intensive investigations into the aetiology of the vasculitis/vasculopathy, including viral infections and autoimmune diseases, were all negative. The follow-up conventional angiography performed 2 months later showed remarkable improvement (figure 1E ). The patient was able to walk without support 5 months after the onset of symptoms. No further symptoms were observed at the 2.5-year follow-up examination. Although the patient demonstrated moderate dysarthria and mild tetraplegia, he was attending high school. Primary angiitis of the central nervous system (PACNS) is an uncommon and idiopathic form of vasculitis confined to the brain and spinal cord. The diagnosis is based on either angiographic or histological evidence of central nervous system (CNS) vasculitis.1 Due to the invasive nature of the CNS biopsy and its high false-negative rates, the diagnosis is often ascertained by angiography without histological verification.2 A beading vessel is generally considered the hallmark of vasculitis.2 Reversible cerebral vasoconstriction syndrome is a newly proposed unifying concept for a group of disorders.3 While our case may fit into this classification, we believe that PACNS is the most appropriate diagnosis based on these symptoms and imaging studies. Basilar artery involvement in PACNS is rare in the paediatric and adult population.2 4 To our knowledge, there have been no reports of PACNS predominantly involving the basilar artery in the paediatric population, with the exception of one mild case.5